Business Ethics in Organizations: An Experimental Examination of Whistleblowing and Personality - Jenny Bartuli; Behnud Mir Djawadi; René Fahr (Institute for the Study of Labor (IZA), 2016)
The present paper suggests an innovative experimental design to study the nature and occurrence of whistleblowing in an employee-organization context. In particular, we aim at identifying whether student subjects in the role of employees are willing to blow the whistle on their managers' decisions to withhold money that is destined for a charitable purpose. Since the sole act of reporting leads to negative financial consequences for both players, the employee faces a conflict between ethical considerations and monetary interests. Of the 111 employee-manager pairings, 88 managers misappropriate the donation funds and 33 employees blow the whistle on their managers' fraudulent behaviors. We use different scales of the HEXACO and the DOSPERT personality inventory to link measures of personality traits to actual behavior which enables us to identify specific characteristics that distinguish whistleblowers from silent observers. We find that the Honesty-Humility factor scale is a strong predictor for whistleblowing. Further, employees who are more altruistic and more aware of ethical issues are more likely to refrain from supporting fraud and report wrongdoing. With the foci on research exploring individual and situational antecedents of whistleblowing, our experimental design offers researchers a new approach to studying organizational behavior of ethical scope under controlled and incentive-compatible conditions.
Keywords: C91; I11; 330; whistleblowing; fraud; organizational wrongdoing; social norms; experimental economics; laboratory experiment